Robust ferromagnetism of ZnO:(Ni+Er) diluted magnetic semiconductor nanoparticles for spintronic applications. Issue 13 (1st July 2021) - Poornaprakash, B.; Ramu, S.; Subramanyam, K.; Kim, Y.L.; Kumar, Mirgender; Pratap Reddy, M. Siva
Abstract: The design and production of co-doped diluted magnetic semiconductor nanostructures for the development of spin-related operating electronic devices have gained considerable attention owing to their formidable characteristics. In this study, we strived to fabricate ZnO, Zn0.98 Ni0.02 O, Zn0.97 Ni0.02 Er0.01 O, and Zn0.96 Ni0.02 Er0.02 O nanoparticles. The successful penetration of Ni and Er ions into the ZnO host material was confirmed through wide-ranging structural analyses. A slight change in the bandgap of ZnO was obtained by doping and co-doping. The photoluminescence spectra revealed that doping and co-doping induced various emissions as well as structural defects in the fabricated nanoparticles. Magnetic hysteresis loops revealed that the ZnO and Zn0.98 Ni0.02 O nanoparticles possessed a paramagnetic nature. However, the Zn0.97 Ni0.02 Er0.01 O and Zn0.96 Ni0.02 Er0.02 O nanoparticles exhibited robust ferromagnetism with clear hysteresis loops. Bound magnetic polaron behavior is well-anticipated to describe the ferromagnetism in the synthesized nanoparticles. Hence, (Ni + Er) co-doping is a promising approach for extending the ferromagnetic nature of the ZnO system for spin-based electronic devices.